Association Between Types of Physical Activity and Risk of Ischemic Heart Disease Based on US Guidelines: A Systematic Review and Meta-Analysis - Jaewoo Cha; Jeehyun Kim; Kwan Hong (SAGE Open)
The mortality rate from ischemic heart disease (IHD) is increasing in both developed and developing countries. The US guidelines for physical activity are known to reduce the risk of IHD; however, no literature review has verified this. This meta-analysis aimed to examine the protective effect of adhering to the US guidelines for physical activity on the IHD risk based on the types of exercise. Six databases, including MEDLINE, EMBASE, Cochrane Library, CINAHL, Scopus, and Web of Science, were searched from January 1, 2000, to November 6, 2022. The literature search was performed on November 6, 2022, at the latest. Only studies designed and conducted in English focusing on IHD-related physical activities in humans were included. The main outcomes were the heterogeneity of studies, overall effects of all types of physical activity, and IHD risk. The random effects model was measured, and a funnel plot was used to examine for publication bias. When the US guidelines for physical activity were not applied, a high level of heterogeneity was found in the effects of physical activity based on its type, with overall effects of 0.764 (odds ratio [OR], 95% confidence interval [CI] [0.737, 0.795]). The effect of physical activity on IHD was 0.593 (OR, 95% CI [0.489, 0.720]). No publication bias was observed. After applying US guidelines for physical activity, a low level of heterogeneity was found in its effects, and the observed OR for myocardial infarction was 0.515 (95% CI [0.401, 0.662]). Each type of exercise had different effects on reducing IHD, and certain beneficial results were observed if US guidelines for physical activity were met.